Community service-learning and cultural-historical activity theory - Taylor, Alison (Canadian Journal of Higher Education, 2014)
This paper explores the potential of cultural-historical activity theory (CHAT), to provide new insights into community service-learning (CSL) in higher education. While CSL literature acknowledges the influences of John Dewey and Paolo Freire, discussion of the potential contribution of cultural-historical activity theory, rooted in the work of Russian psychologist Lev Vygotsky, is noticeably absent. This paper addresses this gap by examining four assumptions associated with activity theory: the rejection of a theory/practice divide, the development of knowledge as a social collaborative activity, the focus on contradictions in and across activity systems, and the interventionist approach aimed at transformation.